An electrochemiluminescent assay for analysis of rabies virus glycoprotein in rabies vaccines - Smith, T. G.; Ellison, J. A.; Carson, W. C.; Ma, X.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Vaccine potency testing is necessary to evaluate the immunogenicity of inactivated rabies virus (RABV) vaccine preparations before human or veterinary application. Currently, the NIH test is recommended by the WHO expert committee to evaluate intra- and inter-lot variation of RABV vaccines; however, numerous disadvantages are inherent concerning cost, number of animals and biosafety requirements. As such, numerous in vitro methods (e.g. antigen-capture ELISA) have been proposed for the evaluation of vaccines based on RABV glycoprotein (G) quality and quantity which correlates with vaccine potency. In this study an antigen-capture electrochemiluminescent (ECL) assay was developed utilizing three murine anti-RABV G monoclonal antibodies (mAb) to quantify RABV G in two commercially available inactivated RABV vaccines, one experimental vaccine, and three purified RABV G preparations. The first mAb was specific for a conformational epitope so that only immunogenic, natively folded G was captured in the assay. Additionally, two mAbs that bind non-competing linear epitopes were employed to evaluate the overall quantity of native and denatured RABV G and for detection. Vaccine efficacy was also assessed in vivo using pre-exposure vaccination of mice followed by peripheral RABV infection. Purified G induced a virus neutralizing antibody (VNA) titer of 4.2 IU/ml and protected 100% of immunized mice; while, an experimental vaccine with low quality and quantity of G induced a VNA titer >0.03 IU/ml and only protected 21% of immunized mice. These preliminary results support the hypothesis that in vivo efficacy may be predicted from the in vitro measurement of RABV G using the ECL assay. Based upon these results, the ECL assay may have utility in measuring potency of RABV vaccines.